2012
DOI: 10.1016/j.metabol.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the hypothalamic-pituitary-adrenal axis in adolescent girls

Abstract: Objective Stress and stress-related concomitants, including hypothalamic-pituitary-adrenal (HPA) axis activation, are implicated in obesity and its attendant co-morbidities. Little is known about this relationship in adolescents. To begin to address this important knowledge gap, we studied HPA axis activity in 262 healthy adolescent girls aged 11, 13, 15, and 17. We hypothesized that obesity would be correlated with increased HPA axis activity and reactivity. Methods Measures of HPA axis activity included 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…There is ongoing debate whether altered cortisol levels are cause or consequence of obesity [9,33]. Obesity has been linked to increased cortisol production, but also lower cortisol levels have been observed due to increased metabolic clearance of cortisol among obese subjects [10,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing debate whether altered cortisol levels are cause or consequence of obesity [9,33]. Obesity has been linked to increased cortisol production, but also lower cortisol levels have been observed due to increased metabolic clearance of cortisol among obese subjects [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only few studies report on the cortisol levels in children in relation to adiposity, blood pressure and glucose tolerance [9]. Lower mean cortisol concentrations were reported in 5- to 16-year-old obese children in comparison with lean children [10].…”
Section: Introductionmentioning
confidence: 99%
“…The circadian rhythm of cortisol seems to be altered in obesity [26], and cortisol levels are increased or decreased depending on the type of obesity and the activity of the HPA axis [27]. A high amount of glucocorticoid receptors in neutrophils enables them to reduce their apoptosis rate in response to dexamethasone [28].…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] However, relatively few studies have examined associations between anxiety/depression, the HPA axis and obesity. 20,[45][46][47] Our previous study, carried out in a clinical population of OC, 20 revealed that overall salivary cortisol concentrations were increased in children with anxiety or depressive symptomatology, as assessed by the STAiC and the CDi questionnaires 48,49 compared to OC without any affective morbidity and to those with anxiety and depression comorbidity. Disturbed cortisol concentrations in these children might be associated with further morbidity.…”
Section: Discussionmentioning
confidence: 96%